Comparisons of Terbuthylazine and Atrazine Rates and Tank Mixtures in Irrigated Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
A comparison of terbuthylazine and atrazine rates alone and in combination with other herbicides in corn was conducted. All herbicides controlled Russian thistle and common sunflower by 90% or more. Preemergence control of green foxtail required a tank mixture of mesotrione (Stalwart C, Stalwart 3W, SA-0070128, and SA-0070129) with terbuthylazine or atrazine to be effective. Both terbuthylazine and atrazine alone provided similar kochia control, but control tended to increase with the addition of mesotrione. Palmer amaranth control was similar among terbuthylazine rates early in the season, but increased as atrazine rate increased. Crabgrass control increased as terbuthylazine rate increased early in the season and with both terbuthylazine and atrazine rates later in the year. Despite differences in weed control, no differences occurred among herbicides for corn yield.
Keywords: residual weed control; triazine